Chinese Medicine in the Management of New and Emerging Infectious Diseases - Viroj Wiwanitkit (KeAi Communications Co., Ltd., 2018)
ABSTRACT: Emerging infectious diseases are an important problem in medicine, and many continue to pose a global threat. However, the management of new and emerging infections is usually difficult due to a lack of knowledge and tools to address the problem. The use of Chinese medicine to manage new and emerging infectious diseases, however, has attracted significant attention. This brief article summarizes and discusses the use of Chinese medicine in the management of new and emerging infectious diseases. Keywords: Chinese Medicine, Emerging, Infection, Prevention, Treatment